The Epidemiological Impact of an HIV/AIDS Vaccine in Developing Countries - Stover, John (The World Bank, 2002)
Many people see an effective preventive AIDS vaccine as the best solution to the HIV/AIDS pandemic. Ten years ago many scientists had hoped that a vaccine would be available by now. Most scientists are still optimistic that vaccines will be developed and many candidates are being tested. Strategies to implement HIV/AIDS vaccination need to be developed to be ready when vaccines do become available. The nature of those programs will depend on the characteristics of each vaccine. How much does it cost? How effective is it? How long does protection last? The answers to these and other questions will help determine issues such as: What will be the impact of the vaccine on the epidemic? Who should be vaccinated? Will an AIDS vaccine be more cost-effective than other prevention measures? Will other measures still be necessary? What will happen to the epidemic if vaccination leads to riskier behavior? How much funding will be needed? Stover, Garnett, Seitz, and Forsythe use two computer simulation models to investigate the effects of various vaccine characteristics and implementation strategies on the impact and cost-effectiveness of vaccines in different contexts. A simulation model is applied to data from rural Zimbabwe and the iwgAIDS model is applied to Kampala (Uganda) and Thailand. The models are used to investigate the effects of efficacy, duration, cost, and type of protection on impact and cost-effectiveness. The models also show the merits of targeting public subsidies to various population groups: all adults, teenagers, high-risk groups, and women of reproductive age. The impact of vaccines on the epidemic is compared with the impact of other prevention interventions such as condom use and behavior change. Finally, the models are used to explore the extent with which behavioral reversals may erode the positive benefits of the vaccine.